Global Disaster Risk Matters - Chen, Jian; Yao, Jiaquan; Zhang, Qunzi; Zhu, Xiaoneng (Management Science, 2023)
This article examines the cross-country asset pricing implications of disaster risk concerns. We construct a new disaster risk index, relying on six news-implied rare disaster proxies of Manela and Moreira (2017) , and show that this index is a powerful predictor for stock returns and other asset returns in international markets both in and out of sample. By further disentangling a global common component from our rare disaster index, we find evidence supporting theories that emphasize globally shared disaster risk as the important driving force of asset price fluctuations. Moreover, we conduct a return decomposition analysis and find that the global disaster risk drives stock returns primarily through the discount rate channel. This paper was accepted by Karl Diether, finance. Funding: This work was supported by National Natural Science Foundation of China [72132002, 71903112, 72192842, U1811462, and 71502152], the Basic Scientific Center of National Science Foundation of China [71988101], the National Social Science Foundation [21&ZD088 and 20&ZD102], SIIFE [2018110262], and the Shanghai University of Finance and Economics [2018110698]. Supplemental Material: The data files and e-companion are available at https://doi.org/10.1287/mnsc.2022.4328 .